Revisiting Metaphors in International Relations Theory - Marks, Michael P. (Springer International Publishing, 2018)
This book presents an analysis of how metaphors are essential elements in the study of international relations. It acknowledges the fact that theory and practice in international relations often rest on common metaphorical concepts which have implications for the ways people around the world pursue their lives. Because of the increased attention metaphors have received as integral elements in political discourse, there is a need to investigate metaphorical concepts that are not neutral in their implications for understanding international relations. Inasmuch as government policy is shaped by metaphorical concepts that originate in the academic realm, and given that scholarly works are therefore partially involved in inspiring policy, the author subjects a range of metaphors in international relations theory to critical interrogation. Michael P. Marks is Professor of Politics at Willamette University in Salem, Oregon, US, and the author of a companion book Metaphors in International Relations Theory (Palgrave Macmillan 2011).